Antioxidant potential of Cydonia oblonga Miller leaves - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2017)
Objective of this study was to determine the total polyphenol content, antioxidant activity properties of the methanolic, ethanolic and aqueous extracts of Cydonia oblonga Miller leaves. Quince leaves have been used as folk medicine in Turkey. Total polyphenol content was determined by Folin-Ciocalteu assay. The antioxidant capacity was determined by ferric ion reducing antioxidant power method (FRAP) and DPPH (2, 2-diphenyl-1 picryl hydrazyl) free radical scavenging method by spectrophotometry. The methanol extract had the highest total phenolic content and the highest antioxidant activity. The results demonstrated that the correlation between total polyphenol content and antioxidant activity which was measured by DPPH and FRAP assays was positive and quince leaves are cheap and natural sources of antioxidants.
Keywords: Cydonia oblonga Miller; quince leaves; Folin-Ciocalteu; DPPH; CAPACITIES; FRUITS